Flexible PDMS Composite Electrodes with Boronic Acid-Modified Carbon Dots for Surface Electrophysiological Signal Recording - Ali, Amaal Abdulraqeb (2024)
Conventional surface electrodes are composed of rigid metals such as Ag/AgCl that are not only harsh to the skin but also irritating if used as wet electrodes. Furthermore, rigid, inflexible surface electrodes can cause patient discomfort when used for long term. To reduce the mechanical mismatch, flexible alternatives to metal electrodes are needed. This study reports the development of highly flexible composite electrodes fabricated from the conductive dopant boronic acid-modified carbon dots embedded in a polydimethylsiloxane matrix. The electrodes were characterized for their structural, electrochemical, and mechanical characteristics and ability to record electrophysiological signals. Furthermore, the composition of these electrodes was varied systematically to obtain the optimal electrochemical and mechanical properties. The best-performing electrode composed of 10% boronic acid-modified carbon dots, 16% glycerol, and 74% polydimethylsiloxane (8:1 elastomer to curing agent) had a smooth surface, a promising conductivity of 9.62×10⁻ᵌ S/cm, an impedance of 964 kΩ at 1 kHz, and a charge storage capacity of 21.4 μC/cm². This electrode had a Young’s modulus (0.0545 MPa), which is compatible with biological tissues’ elasticity. The fabricated electrodes recorded high-quality electrocardiography signals with a promising signal-to-noise ratio (SNR) of 36.75 dB that is comparable to the commercial Ag/AgCl, which had a SNR of 39.98 dB. A similarly good performance was observed with electromyography. Furthermore, the developed flexible surface electrodes maintained their ability to record high quality ECG and EMG over a period of three weeks.